GLP-1 Receptor Agonist Effects on Lipid and Liver Profiles in Patients with Nonalcoholic Fatty Liver Disease: Systematic Review and Meta-Analysis - Shahla Rezaei; Reza Tabrizi; Peyman Nowrouzi-Sohrabi; Mohammad Jalali; Stephen L. Atkin; Khalid Al-Rasadi; Tannaz Jamialahmadi; Amirhossein Sahebkar (Canadian Journal of Gastroenterology and Hepatology)
Aims. This meta-analysis of randomized placebo-controlled clinical trials assessed the effect of glucose-like peptide-1-receptor agonists (GLP-1RA) on the lipid profile and liver enzymes in patients with nonalcoholic fatty liver disease (NAFLD). Materials and Methods. Randomized placebo-controlled trials investigating GLP-1RA on the lipid profile and liver enzymes in patients with NAFLD were searched in PubMed-Medline, Scopus, Web of Science, and Google Scholar databases (from inception to January 2020). A random-effects model and a generic inverse variance method were used for quantitative data synthesis. Sensitivity analysis was conducted. Weighted random-effects meta-regression was performed on potential confounders on lipid profile and liver enzyme concentrations. Results. 12 studies were identified (12 GLP-1RA arms; 677 subjects) that showed treatment with GLP-1RA reduced alanine transaminase (ALT) concentrations (WMD = −10.14, 95%CI = [−15.84, −0.44], P<0.001), gamma-glutamyl transferase (GGT) (WMD = −11.53, 95%CI = [−15.21,−7.85], P<0.001), and alaline phosphatase (ALP) (WMD = −8.29, 95%CI = [−11.34, −5.24], P<0.001). Aspartate aminotransferase (AST) (WMD = −2.95, 95% CI = [−7.26, 1.37], P=0.18) was unchanged. GLP-1 therapy did not alter triglycerides (TC) (WMD = −7.07, 95%CI = [−17.51, 3.37], P=0.18), total cholesterol (TC) (WMD = −1.17 (−5.25, 2.91), P=0.57), high-density lipoprotein (HDL-C) (WMD = 0.97, 95%CI = [−1.63, 3.58], P=0.46), or low-density lipoprotein (LDL-C) (WMD = −1.67, 95%CI = [−10.08, 6.74], P=0.69) in comparison with controls. Conclusion. The results of this meta-analysis suggest that GLP-1RA treatment significantly reduces liver enzymes in patients with NAFLD, but the lipid profile is unaffected.